PERANAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA BAGIAN UMUM DAN KEPEGAWAIAN SEKERTARIAT DAERAH KABUPATEN KUTAI TIMUR - Yuliadi yuliadi (ADMINISTRASI PUBLIK, 2018)
This research is based on leadership carried out by the leadership, in the hope of improving the performance of employees in general office and staffing sekertawat area of East Kutai regency.The purpose of this study is to know how the role of leadership in improving the performance of civil servants and general staff sekertawat districts east kutai district. The type of research or explanation used is descriptive qualitative used to analyze the relationship between research variables. Types of data used are kusioner, observation, interview, and documentation.From the results of research on hypothesis analysis of t-test data obtained t test obtained for leadership variables of 5,535 where t count is greater than t table (5.535 > 1.679), with significant level 0.001 <0.05 then Ho is rejected or Ha accepted, so partial there is a significant positive influence between leadership on employee performance. whereas for R obtained for 0.725, which means that 72.5% of employee performance has a positive contributor to leadership.